Examining the Effects of Reproductive and Productive Teaching Styles Interventions on Primary Schoolchildren. What Implications for Physical Education Teachers? - Domenico Monacis; Sabrina Annoscia; Pierpaolo Limone; Dario Colella (OVS LLC, 2023)
Background. In recent years, the study of the teacher-student relationship in the teaching-learning processes in physical education has had great emphasis. Previous studies have shown that the use of the Spectrum of Teaching Styles can enhance intrinsic motivation, enjoyment, adherence to physical activity and physical activity levels in children and adolescents. Study purpose. The present study aims to assess if a physical education (PE) intervention based on the variations in teaching styles, with reference to productive ones, can also have positive effects on physical fitness. Materials and methods. The sample involved 4 primary school classes (n = 124 children, mean age = 8-10 years) recruited from the SBAM (Health, Wellness, Food Education and Movement at School) Project in Apulia, Southern Italy. The classes were randomly assigned to the Experimental Group (EG) and the Control Group (CG). The EG followed a 5-month experimental intervention based on the variation of teaching styles, while the CG performed regular PE lessons. Physical fitness was assessed with Standing Long Jump (SLJ), 1kg Medicine Ball Throw (MBT), and 20 m sprint (20 m)tests, while two validated questionnaires were used to evaluate physical self-perception (PSP) and enjoyment. A 2x2 (intervention group x time) ANOVA was carried out to assess significant difference and interaction effect pre (t0) and post (t1) intervention protocol. Results. Data analysis showed a significant improvement of physical fitness in both EG and CG, while PSP and enjoyment increased only in EG. Moreover, significant (p < .05) interaction effects were found for 20m sprint, PSP and Enjoyment with low effect size (η2 ~ .20). Conclusions. The results of the present study highlight the effectiveness of a PE intervention based on the variation of teaching styles in improving physical fitness, self-perception, and enjoyment. Moreover, the use of productive teaching styles significantly impacts self-perception and enjoyment that are important mediating factors for guaranteeing better adherence to physical activity.